KASI HUKUM NILAI-NILAI ANTI KORUPSI MELALUI PENDIDIKAN KARAKTER KEPADA ANAK-ANAK WARGA NEGARA INDONESIA DI KAMPUNG PANDAN MALAYSIA - Nanda Arizka Rangkuti; Harisman Harisman (LPPM Universitas Ekasakti, 2024)
Young people are the buds, potential, and generation that will carry forward the ideals of the nation and state in the future. Children must undergo character development, which is a process that involves actions taken to live a worthy life. The character of a country determines how far the country can progress. Children need proper education to develop good character. Becoming better begins with knowledge, which also helps a person to distance themselves from negative traits such as acts of corruption. Corruption is the act of abusing trust in an organization or in something to benefit oneself. Corruption is behavior that can hurt many aspects of people's lives, including income, poverty, and economic growth. This can also cause several problems resulting in significant losses for the country. Therefore, efforts are needed to eradicate corruption, especially for children who are still in elementary school. Give children a definition of corruption and teach them the importance of respecting authority figures. This research aims to teach Indonesian citizen children in Kampung Pandan Malaysia that moral qualities can protect a person from negative things, such as corruption.